Efficacy of topical hydrogel Epigallocatechin-3-gallate against neutrophil cells in perforated dental pulp - Kun Ismiyatin; Ari Subiyanto; Michelle Suhartono; Paramita Tanjung Sari; Olivia Vivian Widjaja; Ria Puspita Sari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: One cause of pulpitis is mechanical trauma such as pulp perforation. The emergency treatment of pulpitis in a clinic uses eugenol. Eugenol in a high concentration causes cytotoxicity, which causes local necrosis and inhibits the recovery process, while in lower doses it can cause oral mucosal hypersensitivity. Due to these side effects, it is worth considering other biocompatible materials with minimal side effects, such as epigallocatechin-3-gallate (EGCG) which is found in green tea. As a polyphenol, EGCG has a radical scavenging ability, which has an effect on reducing the number of neutrophils. The application of EGCG is expected to reduce neutrophils on the second day after injury so the rehabilitation process is completed more quickly and ongoing inflammation and pulp necrosis is prevented. Purpose: To analyse the efficacy of topical hydrogel EGCG in reducing the number of neutrophils after 48 hours in the perforated dental pulp of Wistar rats. Method: 20 Wistar rats were divided equally into four groups, which were designated control (C) and treatment groups (T1, T2, T3). The upper first molar teeth of each rat were perforated and then T1, T2, and T3 were given 60 ppm, 90 ppm and 120 ppm hydrogel EGCG respectively. On the second day, the rats were sacrificed. HPA preparations were made to calculate the number of neutrophils in each group. Data was analysed using Kolmogorov–Smirnov, Levene’s, one-way ANOVA and Tukey HSD test (p<0.05). Results: There were significant differences between T2 and T3 compared with C and T1 (p<0.05), but no significant differences in the comparison of T1 with C and of T2 with T3 (p>0.05). Conclusion: 90 ppm hydrogel EGCG is effective in reducing the number of neutrophils in the perforated dental pulp of Wistar rats.